PENGARUH GRADASI AGREGAT TERHADAP KARAKTERISTIK CAMPURAN ASPAL PANAS AC-WC BERDASARKAN PENGUJIAN MARSHALL - Nofrianto, Hendri; Aprilio, Yogi; Mulyati, Mulyati (Jurnal Teknologi dan Vokasi, 2025)
The development of quality road infrastructure is a key factor in supporting economic growth and inter-regional connectivity. This study aims to analyze the basic characteristics of aggregates and the effect of variations in size and distribution of aggregates on the performance of hot asphalt mixes. Fine and coarse aggregate samples were obtained from two quarry locations, namely Batang Atokan (Pasaman) and Gunung Nago (Padang), by testing using the Marshall method. The results showed that the aggregate from Sungai Atokan Quarry had the highest maximum stability of 1440.99 kg at 5% asphalt content, and showed the highest Marshall Quotient (MQ) value of 371.66 kg/mm. In contrast, Gunung Nago Quarry achieved the highest stability of 1211.93 kg at 7% asphalt content, but experienced a decrease in the VIM value below the specification limit at high asphalt content, indicating a risk of bleeding. The optimum asphalt content value for each quarry was 6.5% for Sungai Atokan and 6.0% for Gunung Nago. Comparative analysis shows that the mixture from the Atokan River Quarry is stiffer, more resistant to deformation, and suitable for heavy traffic, while the mixture from Mount Nago is more plastic and sensitive to excess asphalt content. The results of this study are expected to serve as a technical reference in aggregate selection and hot asphalt mix planning to improve road pavement quality in West Sumatra.